2018 Vegetable Production Handbook Chapter 8: Eggplant Production - Eugene J. McAvoy; Nathan S. Boyd; Monica Ozores-Hampton; Pamela D. Roberts; Johan Desaeger; Joseph W. Noling; Hugh A. Smith (EDIS, 2018)
This 27-page fact sheet is chapter 8 of the 2018 Vegetable Production Handbook. Written by Eugene J. McAvoy, Nathan S. Boyd, Monica Ozores-Hampton, Pamela D. Roberts, Johan Desaeger, Joseph W. Noling, and Hugh A. Smith, and published by the Horticultural Sciences Department, 2018.